PENGARUH KARAKTERISTIK PEKERJAAN DAN MODAL PSIKOLOGI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN MODERASI PERSON ORGANIZATION FIT (PO FIT) (Studi Pada Dinas Pendapatan, Pengelolaan, Keuangan, Dan Aset Daerah Kabupaten Pati) - Rachmawati, 1352020058; Suko Priyono, Bambang (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study has aimed to examine and to analyze the influence job characteristic and psychological capital for organizational citizenship behavior on moderation person organization fit at Dinas Pendapatan, Pengelolaan Keuangan dan Aset Kabupaten Pati. Data collection used survey method for 103 respodens. They were public servant on Dinas Pendapatan, Pengelolaan Keuangan dan Aset Kabupaten Pati with census methode. The technique of data testing used statistical method, they covered validity test, reliability test, multiple regression analysis, t-test and moderation test. They were used to test and to prove hypotheses ofÂ study. The result of validity test pointed out KMO value was 0,683 for job characteristic variable, 0,731 for psychological capital, 0,690 for person organization fit variable, and 0,793 for organizational citizenship behavior variable. They were reliable in test, so alpha cronbach value was over 0,7. Based on resulting of their analysis, its examining pointed out job characteristic and organizational citizenship behavior influenced positive and significant for psychological capital and organizational citizenship behavior. While person organization fit moderate the influence job characteristic and organizational citizenship behavior and person organization fit moderate the influence psychological capital and organizational citizenship behavior. Keywords: Job Characteristic, Psychological Capital, Person Organization Fit, Organizational Citizenship Behavior